Promoting UG-Technopark In Advancing Hospitality Studies: Challenges And Opportunities - Akhirson, Armaini; Setyawati, Murni; Sri Sumardillah, Dewi; Davronov, Istamkhuja (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
Gunadarma University' as one of the biggest private university in Indonesia has Technopark located in Cianjur, West Java, it is equipped with facilities such as glamping sites, a kitchen, meeting hall and a park featuring various herbs, spices, and plants, holds significant potential for enhancing hospitality studies. However, these resources are currently underutilized by students and faculty, limiting their effectiveness in advancing academic and practical learning. This study explores the challenges and opportunities of utilizing UG Technopark to enhance hospitality education. Using a qualitative approach, in-depth interviews were conducted with faculty members, students, and industry stakeholders, also observation to gather insights into the current limitations and potential areas for improvement. The findings highlight key challenges include geographical distance, limiting regular use by students and faculty. However, UG Technopark provides valuable hands-on experiences and opportunities for interdisciplinary collaboration. The findings highlight the potential for stronger university-industry partnerships, strategic curriculum alignment, and contributions to sustainable hospitality practices, benefiting both the university and the broader community.